Social capital of local communities in the water resources management: an insight from Kepulauan Riau. Issue 1 (March 2020) - Yudiatmaja, W E; Yudithia; Samnuzulsari, T; Suyito; Edison
Abstract: This paper draws the process of water resources management of local communities by using the social capital point of view. By using a comparative case study, this research was conducted in two regions in Kepulauan Riau, Senggarang and Mantang. Social capital of local communities, such as norms, trust, beliefs, and gotong-royong play a significant role in the process of governing water resources in different ways. This paper contributes to the study of water resources management by recognizing the social capital of local communities. In practical terms, this study is also valuable to the practice of water resources management in the local context in Indonesia. The theoretical, methodological, and practical implications of the study are discussed.